2012
DOI: 10.1093/pubmed/fds028
|View full text |Cite
|
Sign up to set email alerts
|

School toilets: facilitating hand hygiene? A review of primary school hygiene facilities in a developed country

Abstract: These results suggest that a significant number of New Zealand children do not currently have access to high quality hygiene facilities at school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…Third, research should include process evaluation to refine interventions and establish intervention acceptability and fidelity. Studies which have done process evaluations 40 57 have identified barriers to hand hygiene including access to adequate sanitary facilities (even in high-income countries), suggesting that provision of hygiene products and education may be insufficient to achieve effective infection prevention and control and more robust studies of complex, multicomponent interventions are required. Fourth, studies should evaluate cost, cost-effectiveness and intervention sustainability in educational settings.…”
Section: Discussionmentioning
confidence: 99%
“…Third, research should include process evaluation to refine interventions and establish intervention acceptability and fidelity. Studies which have done process evaluations 40 57 have identified barriers to hand hygiene including access to adequate sanitary facilities (even in high-income countries), suggesting that provision of hygiene products and education may be insufficient to achieve effective infection prevention and control and more robust studies of complex, multicomponent interventions are required. Fourth, studies should evaluate cost, cost-effectiveness and intervention sustainability in educational settings.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is critical to understand the current knowledge, attitude and behaviour of good hygiene and its impact on the increased diarrhoea illness in a residential community of a developed country. In addition, most of the current understanding of the knowledge, attitude and behaviour on hygiene was significantly focused on less developed communities [20][21][22][23][24], and very limited in the well-developed communities [11,25]. Therefore, we aim to determine the current knowledge, attitude and behaviour of good hygiene as well as risk factors of diarrhoea disease in a developed community in Singapore, where clean water and soap are easily available and affordable.…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to test whether the addition of hand sanitiser in primary school classrooms compared with usual hand hygiene (use of soap and water, mainly in school bathrooms) would reduce illness absences in primary school children in New Zealand. We chose to use hand sanitiser as our hand hygiene modality in preference to increasing use of existing facilities because school bathroom hand-washing facilities are of variable quality [16] , [17] , which might be a barrier to attempts to increase hand-washing. Improving and maintaining bathroom facilities in a large number of schools would be a major undertaking, and hand sanitiser is an acceptable alternative to hand-washing with soap and water for children [18] .…”
Section: Introductionmentioning
confidence: 99%